Application of science and technology for farmer groups facing the cabbage caterpillar explosion in The Village of Sembalun Lawang, East Lombok Regency. - Suripto Suripto; Dedy Suhendra; Sukiman Sukiman (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The implementation of science and technology for community (IbM) farmer groups who are facing the problem of the cabbage caterpillar population explosion was carried out in Sembalun Lawang Village, East Lombok Regency. The IbM activity was designed based on the agreement between the IbM team and the Village Head of Sembalun Lawang together with the Sangka Bira Farmers Group and the Sebun Kedit Farmers Group in Sembalun Lawang Village. IbM activities are carried out with the stages of socialization, practice, and tutorials with various media used including blackboards, LCDs, manuals (leflet), seeds, saplings, specimens, and leaf dry powder of jayanti plants (S. sesban). Partners also provide media for this IbM activity, which includes cabbage plantations and water facilities. The results achieved at this stage are that farmers in Sembalun Lawang Village recognize jayanti plants as a source of natural insecticides, are skilled at drying leaves properly and making leaf solutions from Jayanti plants and trying to apply them as natural insecticides to control cabbage caterpillars on cabbage plants. The results of trials by farmers showed that direct administration of 50 ppm Jayanti leaf solution could kill 52 to 56% of cabbage caterpillars on cabbage plants. If the Jayanti leaf solution was stored for the previous 24 hours, then 50 ppm of the solution could only kill 15 to 16% of cabbage caterpillars. After participating in this IbM activity, the farmers were also able to identify the type of parasitoid insect, Diadegma semiclausum, which can control the cabbage caterpillar population. The outputs of this IbM activity include 1) Farmer's Guide Book (leflet) Making and Application of Insecticides from Jayanti Plants for Integrated Control of Cabbage Caterpillars, 2) IbM results publication at national seminars (poster presenter certificate), and 3) Publication of IbM results in national scientific journal (submitted). The next stage to be carried out is to monitor and continue the mentoring (tutorial) by the team to IbM participants in the implementation of Jayanti plant cultivation and the manufacture and use of Jayanti insecticide in controlling cabbage caterpillars on cabbage plantations in Sembalun Lawang Village, East Lombok Regency.The implementation of science and technology for community (IbM) farmer groups who are facing the problem of the cabbage caterpillar population explosion was carried out in Sembalun Lawang Village, East Lombok Regency. The IbM activity was designed based on the agreement between the IbM team and the Village Head of Sembalun Lawang together with the Sangka Bira Farmers Group and the Sebun Kedit Farmers Group in Sembalun Lawang Village. IbM activities are carried out with the stages of socialization, practice, and tutorials with various media used including blackboards, LCDs, manuals (leflet), seeds, saplings, specimens, and leaf dry powder of jayanti plants (S. sesban). Partners also provide media for this IbM activity, which includes cabbage plantations and water facilities. The results achieved at this stage are that farmers in Sembalun Lawang Village recognize jayanti plants as a source of natural insecticides, are skilled at drying leaves properly and making leaf solutions from Jayanti plants and trying to apply them as natural insecticides to control cabbage caterpillars on cabbage plants. The results of trials by farmers showed that direct administration of 50 ppm Jayanti leaf solution could kill 52 to 56% of cabbage caterpillars on cabbage plants. If the Jayanti leaf solution was stored for the previous 24 hours, then 50 ppm of the solution could only kill 15 to 16% of cabbage caterpillars. After participating in this IbM activity, the farmers were also able to identify the type of parasitoid insect, Diadegma semiclausum, which can control the cabbage caterpillar population. The outputs of this IbM activity include 1) Farmer's Guide Book (leflet) Making and Application of Insecticides from Jayanti Plants for Integrated Control of Cabbage Caterpillars, 2) IbM results publication at national seminars (poster presenter certificate), and 3) Publication of IbM results in national scientific journal (submitted). The next stage to be carried out is to monitor and continue the mentoring (tutorial) by the team to IbM participants in the implementation of Jayanti plant cultivation and the manufacture and use of Jayanti insecticide in controlling cabbage caterpillars on cabbage plantations in Sembalun Lawang Village, East Lombok Regency.